Community Participation in Wind Energy Developments in Finnish Lapland: An Energy Justice Perspective - Rehder, Sydney (University of North Carolina at Chapel Hill Graduate School, 2024)
This thesis seeks to better understand community participation and energy justice in green energy transitions. Just transitions, a fair and equitable approach to transitioning from a fossil fuel-based economy to a sustainable, low-carbon economy, offer an opportunity to bring justice into energy transitions. The concept of just transitions has recently gained traction, especially in the European Union and the European Green Deal. Energy justice is an extension of the idea of just transitions, applying ideas of justice and equity to global energy systems. By examining local energy transitions in Finnish municipalities through an energy justice lens, this thesis provides insights into community involvement in the Arctic energy transition. Increased participation indicates a greater presence of justice in the energy system. This thesis concludes that the role of local governance is critical in implementing just transitions and that bottom-up governance can allow for more participatory opportunities. Master of Arts